Visualisasi Dimensi Kewaktuan dalam Gambaran Relief Cerita, (Studi Kasus Relief Cerita Krêsna di Candi Prambanan) - Andri Restiyadi (Berkala Arkeologi Sangkhakala, 2009)
AbstractStory’s relief is a combination of narrative and visual art which function as a communication media for people in the past. It moreover consists of social culture information, story’s relief has also left tracks of the methode of an artist for framing the story in visual form. One thing that insteresting in this regard is time dimension visualization. Time dimension is extremely difficult visualized in the form of images without any information in the form of the verbal. Yet, the artist of the past were able to overcome these problems by way of a typical visualization without including any verbal information.